2020
DOI: 10.5194/amt-13-6593-2020
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of numerical weather prediction model analysis during fog conditions through the assimilation of ground-based microwave radiometer observations: a 1D-Var study

Abstract: Abstract. This paper investigates the potential benefit of ground-based microwave radiometers (MWRs) to improve the initial state (analysis) of current numerical weather prediction (NWP) systems during fog conditions. To this end, temperature, humidity and liquid water path (LWP) retrievals have been performed by directly assimilating brightness temperatures using a one-dimensional variational technique (1D-Var). This study focuses on a fog-dedicated field-experiment performed over winter 2016–2017 in France. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…In this study, the focus is on the combination of the MWR and RASS observations in the retrievals to improve the accuracy of the temperature profiles in the lowest 3 km compared to physical retrieval approaches that do not include the information from RASS measurements. Some studies have used analyses from numerical weather prediction (NWP) models as an additional constraint in these variational retrievals (e.g., Hewison, 2007;Cimini et al, 2006Cimini et al, , 2011Martinet et al, 2020); however, we have elected not to include model data in this study because we wanted to evaluate the impact of the RASS profiles on the retrievals from a purely observational perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the focus is on the combination of the MWR and RASS observations in the retrievals to improve the accuracy of the temperature profiles in the lowest 3 km compared to physical retrieval approaches that do not include the information from RASS measurements. Some studies have used analyses from numerical weather prediction (NWP) models as an additional constraint in these variational retrievals (e.g., Hewison, 2007;Cimini et al, 2006Cimini et al, , 2011Martinet et al, 2020); however, we have elected not to include model data in this study because we wanted to evaluate the impact of the RASS profiles on the retrievals from a purely observational perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Low cloud whose base is descending is very likely to be observed before an instance of cloud base lowering (CBL) fog. A Vaisala CL-31 ceilometer (Martucci et al, 2010) was used to measure the cloud base height. This uses a pulse lidar to sense the cloud base and is capable of sensing up to three layers simultaneously with a range from 0 to 7.6 km.…”
Section: Other Instrumentsmentioning
confidence: 99%
“…In 1D-Var systems, the integrated liquid water content, Liquid Water Path (LW P ) can be included in the control vector x as initially proposed by Deblonde and English (2003) and more recently used by Martinet et al (2020). A first experimental set-up has been defined where the minimization is performed with the control vector being (T, q v , LW P ).…”
Section: The Components Of the 1d-varmentioning
confidence: 99%
“…This is particularly the case during fog conditions with much shorter vertical correlation length-scales at the lowest levels and large positive cross-correlations between temperature and specific humidity (Ménétrier and Montmerle, 2011). In this context, Martinet et al (2020) have demonstrated that humidity retrievals could be significantly degraded if sub-optimal background error covariances are used during the minimization. New ensemble approaches allow a better approximation of background error covariance matrices but rely on the capability of the ensemble data assimilation to correctly represent model errors, which might not always be the case during fog conditions.…”
Section: Introductionmentioning
confidence: 99%